A memristor-based chaotic-masking for analog spread-spectrum communication - Muhammad Taher Abuelma’atti; Abdullah Yousef Alnafisa (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a simple chaotic-masking system. The system uses a chaos generator built around a grounded memristor. The memristor is emulated using the current-feedback operational amplifier (CFOA). At the sending end the signal is masked by adding chaos. At the receiving end the signal is recovered by subtracting the chaos. The performance of proposed system is investigated using sinusoidal and square wave signals.